PeHVA22 gene family in passion fruit (Passiflora edulis): initial characterization and expression profiling diversity - Hou, Zhimin; Liang, Jianxiang; Cai, Xinkai; Lin, Jingting; Wang, Xiaomei; Liu, Ruoyu; Lu, Lin; Chai, Gaifeng; An, Chang; Chen, Shengzhen; Qin, Yuan; Zheng, Ping (Frontiers in Plant Science, 2024)
Passion fruit, an economically valuable fruit crop, is highly vulnerable to adverse climate conditions. The HVA22 genes, recognized as abscisic acid (ABA) and stress-inducible, play vital roles in stress response and growth regulation in diverse eukaryotic organisms. Here, six HVA22 genes were firstly identified in passion fruit genome and all predicted to be localized within the endoplasmic reticulum.Phylogenetic analyses showed that all PeHVA22s were divided into four subgroups.PeHVA22 genes clustered in the same subgroup were relatively conserved, while the gene structure characteristics of PeHVA22s from different subgroups varied significantly. PeHVA22A and PeHVA22C closely clustered with barley HVA22 in Group II, were also induced by ABA and drought stress treatment, suggesting conserved roles similar to barley HVA22. Meanwhile, most PeHVA22s exhibited induced expression post-drought treatment but were suppressed under salt, low and high-temperature conditions, indicating a unique role in drought response. Additionally, PeHVA22s displayed tissue-specific expression patterns across diverse tissues, except for PeHVA22B which maybe a pseudogene. Notably, PeHVA22C, PeHVA22E, and PeHVA22F predominantly expressed in fruit, indicating their involvement in fruit development. Almost all PeHVA22s showed variable expression at different developmental stages of stamens or ovules, implying their roles in passion fruit's sexual reproduction. The intricate roles of PeHVA22s may result from diverse regulatory factors including transcription factors and CREs related to plant growth and development, hormone and stress responsiveness. These observations highlighted that PeHVA22s might play conserved roles in ABA response and drought stress tolerance, and also be participated in the regulation of passion fruit 非突出显示 设置格式[ZhengPing]: